Exporting political theology to the diaspora: translating Rabbi Abraham Isaac Kook for Modern Orthodox consumption - Asscher, Omri (Meta, 2020)
The recent boost in English translations of Rabbi Abraham Isaac Kook (1865-1935), the undisputed father of religious Zionism, may be considered a revealing juncture between Israeli and American Modern Orthodox Jewish communities. Upon establishing the features of theological translation in this homeland-diaspora framework, my paper offers a discussion of a dominant translation trend of Kook’s thought in the 1990s, an ideologically motivated “export” of texts which has been largely determined by the transnational movement of people. The translators were American rabbis who emigrated and settled in Israel and the main target audience for the translations was the growing number of young American Jews making the one-year study visit in Israeli yeshivas before returning to American college life. The translations, I argue, were framed as a political polemic on the part of right-wing religious Zionism, aimed at promoting a highly nationalist, topical political interpretation of Kook’s suggestive Hebrew works among English-speaking Modern Orthodox Jews, particularly those making the increasingly popular study visit in Israeli yeshivas – visits that have been associated with the persistent “slide to the Right” of Modern Orthodox Judaism in America in recent decades.